2005
DOI: 10.2220/biomedres.26.21
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of high-flow or removal of flow cannot stop high-flow induced endothelial proliferation

Abstract: Endothelial cells (ECs) are activated in response to high-fl ow. Our previous studies using arteriovenous fi stula (AVF) model have demonstrated that high-fl ow in blood vessels induces an early and rapid proliferation of ECs before arterial dilatation. Here, we investigated the proliferation of ECs, which had once been stimulated by high-fl ow loading, in a situation without the infl uence of high-fl ow. First, we induced high-fl ow in the rabbit common carotid artery by using AVF. Then, we removed the infl u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…We here show a pro-survival, proproliferation response of HWSS, given the results of gene expression analysis and the reported roles of the miRNAs upregulated under this condition. This is in-line with previous reports on the proliferative impact of HWSS on ECS (Yamauchi et al, 2005). This could also explain our previous report, in which a patient developed a daughter sac in a cerebral aneurysm followed over a course of several years (Sugiyama et al, 2016).…”
Section: Hsa-mir-1268asupporting
confidence: 93%
“…We here show a pro-survival, proproliferation response of HWSS, given the results of gene expression analysis and the reported roles of the miRNAs upregulated under this condition. This is in-line with previous reports on the proliferative impact of HWSS on ECS (Yamauchi et al, 2005). This could also explain our previous report, in which a patient developed a daughter sac in a cerebral aneurysm followed over a course of several years (Sugiyama et al, 2016).…”
Section: Hsa-mir-1268asupporting
confidence: 93%
“…More recently, Thoma's hypothesis of the remodeling of normal intimal hyperplasia has been further investigated and subjected to experimental testing. It has been unequivocally confirmed in a number of elegant studies [ 159 - 173 ], leading to advanced modeling such as the Glagov and Kamiya-Togawa models. A very powerful conformation of the "slow flow" effects on expansion of hyperplasia and arterial narrowing was reported by Karino-Goldsmith group [ 174 - 181 ].…”
Section: Introductionmentioning
confidence: 91%
“…Richard Thoma was the first to enunciate a conceptually motivated approach to the problem. In my view, this was the foundation of his tremendous personal achievement in the field of arterial pathology, and for the extremely important observations and conclusions made by scientists whom his ideas inspired [ 159 - 161 , 163 - 173 , 181 - 184 , 187 , 188 ].…”
Section: Introductionmentioning
confidence: 93%
“…Multiple observations have demonstrated that cells participating in this morphogenesis can be of different origins. As to regulations directing normal and pathological morphogenesis, a shear stress was suggested as the major factor [168-178]. In addition, I hypothesized that the arterial blood-tissue interface itself (as a topological entity) contributes to this morphogenesis, and the enhanced proliferative capacity of the arterial intima is a reflection of phenotype selection [69,179] (though these statements do not suggest mechanisms of regulation).…”
Section: Discussionmentioning
confidence: 99%